Da’i Strategies in Delivering Da’wah for Adolescents’ Moral Improvement in Tanjuang Alam Nagari - Zainil Bakhri; Irman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This research examines the strategies of Islamic preachers (da’i) in delivering da’wah to improve the moral character (akhlak) of adolescents in Nagari Tanjuang Alam, Tanah Datar Regency, West Sumatra. The study is motivated by the phenomenon of declining adolescent morality, marked by weakened religious awareness, reduced social ethics, and increasing influence of digital media and Western popular culture. This study employs a qualitative descriptive method. Data were collected through in-depth interviews, observation, and documentation involving 17 informants: seven da’i, four mosque administrators, and six adolescents. Data analysis followed Miles and Huberman’s interactive model. The main theoretical framework is Mohammad Ali Aziz’s da’wah theory, encompassing three strategies: da’wah bil lisan (verbal), bil hal (exemplary conduct), and bil kitabah (written/digital). Findings indicate that bil lisan strategy—implemented through weekly youth religious gatherings, religious lectures, and personal mentoring with persuasive approaches—effectively improves adolescents’ Islamic knowledge yet requires consistency. The bil hal strategy, realized through moral exemplification and direct involvement in social activities, proves the most effective in forming behavioral change. The bil kitabah strategy, conducted via social media platforms (Facebook, TikTok, Instagram), has yielded positive responses but remains suboptimal and requires greater creativity and consistency. These three strategies are complementary and collectively contribute to adolescents’ moral improvement in the community.